Translators to weave with the non-humans - Karine Bonneval (Quantitative Plant Biology, 2022)
My visual artworks propose ways of being in the world—the world that humans share with non-humans. By developing projects such as breathe with a tree or listen to soil, I wish my installations to be experienced as translators. Those art projects are the result of collaborations with different teams of scientists. Together we found technological tools that could be used in art installations. These hybridizations between art and science sometimes mischievously divert technology, and instead, offer us aesthetic work with its roots deep in traditional arts and crafts knowledge. With them we can—for a moment—share time with plants, and be in dialogue with air, soil and gravity. The first project, Dendromacy, an experimental movie, was designed with a specific cooled lens thermal camera. The second one, Listening to the soil, a sounded ceramic installation started from bioacoustics recordings of the soil mega and meso-fauna.